Installation and technique of experimental investigations of composite materials based on beryllium - Kenzhin Ye.А.; Kulsartov Т.V.; Kenzhina, I.Ye.; Udartsev, S.V. (Recent Contributions to Physics, 2023)
Interest in beryllium-based composite materials has emerged recently, when intermetallic compounds such as titanium beryllide Be12Ti began to be considered as a promising material for neutron multiplication in thermonuclear fusion facilities, such as ITER and DEMO. Titanium beryllide stands out from other beryllides because it has the highest neutron multiplication rates and also has the added benefit of being more thermally stable than beryllium metal. Titanium beryllide interacts much weaker with water vapor, excluding the possibility of the formation of explosive hydrogen in the blanket body, is less prone to gas swelling, and, unlike metallic beryllium, retains a smaller amount of accumulated tritium. It has also been confirmed that the compatibility of titanium beryllide with structural materials is much higher than that of beryllium. To use titanium beryllide, it is important to study the parameters of its interaction with hydrogen isotopes. One of the most well-known methods for is the method of thermal desorption spectroscopy (TDS). The objective of this paper is the development of a specialized experimental setup for TDS research and the development of a methodology for performing experiments. The results of methodical experiments are presented, in which the procedures for saturation of samples in a deuterium medium and procedures for conducting TDS experiments were worked out. Methodical experiments on studying the parameters of the interaction of deuterium with samples of monolithic titanium beryllide were carried out on the material produced by Ulba Metallurgical Plant JSC, saturated in deuterium at atmospheric pressure and a sample temperature of 973 K. linear heating rates of 10 and 20 K/min. Based on the results of the development of the technique for conducting experimental studies of titanium beryllide, a differential mode of the TDS method was recommended. In this case, it is necessary to use a hydrogen isotope, deuterium, as a control probe.